2019
DOI: 10.22219/jch.v4i1.9166
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Penerapan Pendidikan Multikultural Dalam Menciptakan Toleransi Antar Umat Beragama Di SMP Immanuel Batu

Abstract: ABSTRAK             Penelitian ini bertujuan untuk menganalisis (1) penerapan pendidikan multikultural di SMP Immanuel Batu; (2) toleransi antar umat beragama di SMP Immanuel Batu; (3) faktor pendukung dan penghambat penerapan sikap toleransi atar umat beragama di SMP Immanuel Batu. Rumusan masalah dalam penelitian ini antara lain:(1) bagaimana penerapan pendidikan multikultural di SMP Immanuel Batu; (2) bagaimana toleransi antar umat beragama di SMP Immanuel Batu; (3) apa faktor pendukung dan penghambat dalam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Differences in beliefs do not dampen the harmony between religious communities that accept each other, respect each other, help each other, and work together to achieve common goals (Rusydi & Zolehah, 2018). Tolerance is also an attitude where people can live side by side and respect each other's differences, especially differences in belief or religion (Adawiyah et al, 2019). Therefore, the value and concept of religious tolerance are related to the attitude of giving freedom, independence, and human rights to everyone to embrace their religion and accept their existence in a pluralistic society (Muhid & Fadeli, 2018).…”
Section: Nature Of Tolerance In Pluralismmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences in beliefs do not dampen the harmony between religious communities that accept each other, respect each other, help each other, and work together to achieve common goals (Rusydi & Zolehah, 2018). Tolerance is also an attitude where people can live side by side and respect each other's differences, especially differences in belief or religion (Adawiyah et al, 2019). Therefore, the value and concept of religious tolerance are related to the attitude of giving freedom, independence, and human rights to everyone to embrace their religion and accept their existence in a pluralistic society (Muhid & Fadeli, 2018).…”
Section: Nature Of Tolerance In Pluralismmentioning
confidence: 99%
“…Indonesia is an archipelagic country with a population of over 237 million and 1,340 ethnic groups. It is a nation of various cultures, languages, ethnicities, and religions due to its geographical conditions, stretching from Sabang to Merauke (Adawiyah et al, 2019). There are six officiallyrecognized religions in Indonesia, namely Islam, Protestant Christianity, Catholicism, Hinduism, Buddhism, and Confucianism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indonesia has at least 300 ethnic groups, and 1.340 tribes (Indonesia, 2017). Tolerance is a stance where individuals respect and honour each other (Kemenag, 2023) Tolerance is not only restricted to religion and race context but also differences in language, socioeconomic, family situation, disabilities, physical abilities, respect for other people's weaknesses, etc (Adawiyah, 2019;Rahmawati & Fatmawati, 2016). Research about tolerance in Indonesia was often conducted, for example, a study by Litbang Kompas in 2022 revealed that at least 62% of respondents considered Indonesians as intolerant (Widi, 2022).…”
Section: Introductionmentioning
confidence: 99%